Simulation analysis and experimental demonstration of velocity vector field of medium flow in double mass vibration mill. (2nd January 2016) - Yang, Xiaolan; Zhang, Na; Liu, Jifeng; Wang, Zhijing; Zhou, Yajun
Abstract: To resolve the technical issue that very hard particle is difficult to be refined, the mesoscopic numerical simulation of discrete medium flows based on Particle Flow Code was established. Four combinations of frequency and amplitude were set to simulate the medium flow, and the images of velocity gradation and velocity vector field have been obtained. Results show that the energy in medium flow was transmitted faster, and the effect of impact and shear forces among medium was stronger in the mode with mid-frequency and large amplitude. To verify the simulation results, the diamond ultrafine grinding is done in both normal and new vibration mills with the same basic parameters. Through size detecting in MS 2000 laser particle sizer and recording by high-speed photographic Mikrotron Gmbh, the results are basically consistent with the simulation analysis of velocity vector. Compared with other modes, the kinetic and strain energy of medium flow in the mode of mid-frequency with large amplitude is increased up to 0.3–5 times, and energy-lacking area is reduced by 8–20%; the effect of particle refinement and narrowing distribution is obvious. It becomes a positive technical progress in the field of very hard particle vibration grinding and micronano refinement.